Optimizing Method for Potato Meristem Vitrification - Stribul, T. F.; Shevchenko, N. A.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2005)
Comparative data of potato meristem cryopreservation according to different freezing protocols are shown. The possibility to vary conditions for apexes (shoot-tips) preparing to cryopreservation using vitrification method was investigated. There was proposed a vitrification PVSN solution with modified composition. A possibility to exclude some steps of preliminary meristem preparing to freezing with no loss in integrity of cryopreserved material was established.